Pseudoxanthoma Elasticum a Rare Genetic Disorder : A Case Report - Shashwata Raj Pandit; Anupa Khadka; Ayush Jha; Rima Shrestha; Ravina Bade Shrestha (Nepal Journal of Dermatology, Venereology & Leprology)
Pseudoxanthoma elasticum (PXE) is a rare hereditary condition marked by the accumulation of fragmented and calcified elastic fibers in the body's tissues, leading to skin, vascular, and ocular involvement. In clinical practice, the most prevalent and typically earliest indication of PXE is observed through skin manifestations, which include laxity and the presence of yellowish papules and plaques. Here we report a case of a 40-year-old woman from Nepal presenting with yellowish multiple papules and plaque around the neck and axilla for 20 years, slowly increasing in size and number. A skin biopsy revealed fragmented eosinophilic elastic fibers in the dermis, consistent with PXE. Echocardiography, slit lamp, and indirect ophthalmoscopic examination were done.